REVISÃO CRÍTICA DA TESE DO "SUICÍDIO REVOLUCIONÁRIO" (Revista de História Regional, 2007)
This article brings up utmost information about the guerrillas'war in Brazil between the 60's and 70's, being the Araguaia's Guerrilla its background. With no intention of an exhaustive revision on the literature, it aims to analyze the meaning of the diagnosis produced in the 80's and 90's, known as what is called the "revolutionary suicide" and the search for the "reasons for defeat" of the "Leftist" revolutionary project, which would have been the adventure of Brazil's armed revolution. Through talks with authors, the conclusion reached was that the self-critics that followed this direction were under the influence of a new political-strategic basis to the Brazilian society leaded by PT. The main authors from self-critics thoughts were directly or indirectly linked to this party organization, fact that followed the evaluation of the move to deductions strongly influenced by the dilemmas'consolidation from the Democratic Transition and the standing of a new social-democratic project for the country, which is still in power nowadays.